2014
DOI: 10.1007/s00787-014-0602-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effectiveness of electroconvulsive therapy in adolescents with schizophrenia spectrum disorders

Abstract: To compare a sample of adolescents with schizophrenia spectrum disorders (SSD) treated with either ECT or antipsychotics (AP) alone at long-term follow-up. Patients diagnosed with SSD (n = 21) treated with ECT due to resistance to AP or catatonia under the age of 18 years (ECT group), were compared to a randomly selected group of patients with SSD treated only with AP (non-ECT group) (n = 21) and matched for age, gender, diagnosis and duration of illness. Baseline data were gathered retrospectively from medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Patients treated with both ECT and antipsychotic medications had 74% response rates versus 50% response rates in those with medication alone, based on greater than 30% improvement in the Positive and Negative Syndrome Scale scores. Twenty-one adolescents diagnosed with schizophrenia spectrum disorders treated with ECT because of resistance to antipsychotics or catatonia were assessed at follow-up (mean, 5.5 years; range, 2–9 years) after treatment and found comparable with a matched group of nonresistant to antipsychotics 61 . A prospective naturalistic study by Suzuki et al 62 examined the short-term effects of ECT in 7 young adults with neuroleptic-refractory first-episode schizophrenia, which showed significant improvement on the Global Assessment of Functioning (GAF) and the Brief Psychiatric Rating Scale after treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients treated with both ECT and antipsychotic medications had 74% response rates versus 50% response rates in those with medication alone, based on greater than 30% improvement in the Positive and Negative Syndrome Scale scores. Twenty-one adolescents diagnosed with schizophrenia spectrum disorders treated with ECT because of resistance to antipsychotics or catatonia were assessed at follow-up (mean, 5.5 years; range, 2–9 years) after treatment and found comparable with a matched group of nonresistant to antipsychotics 61 . A prospective naturalistic study by Suzuki et al 62 examined the short-term effects of ECT in 7 young adults with neuroleptic-refractory first-episode schizophrenia, which showed significant improvement on the Global Assessment of Functioning (GAF) and the Brief Psychiatric Rating Scale after treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-one adolescents diagnosed with schizophrenia spectrum disorders treated with ECT because of resistance to antipsychotics or catatonia were assessed at follow-up (mean, 5.5 years; range, 2-9 years) after treatment and found comparable with a matched group of nonresistant to antipsychotics. 61 A prospective naturalistic study by Suzuki et al 62 examined the short-term effects of ECT in 7 young adults with neuroleptic-refractory first-episode schizophrenia, which showed significant improvement on the Global Assessment of Functioning (GAF) and the Brief Psychiatric Rating Scale after treatment. In a case study, a combination of clozapine and maintenance ECT allowed a 17-year-old adolescent boy with intractable catatonic schizophrenia to exhibit enough clinical improvement to regain some autonomy with experiencing moderate adverse effects in a report by Consoli et al 63 Electroconvulsive therapy has also been used in combination with medication in cases of catatonic schizophrenia.…”
Section: Evidence For Ect In Psychosis and Schizophreniamentioning
confidence: 99%
“…22 In comparison, in youth, use of lorazepam to treat acute catatonic episodes is associated with response rates of approximately 70%. 48 Flamarique et al 49 conducted a prospective study in adolescents and found that combination regimen with antipsychotics and ECT in treatmentresistant schizophrenia spectrum disorder or catatonia is as effective in the long term as antipsychotics alone in nonresistant patients.…”
Section: Discussionmentioning
confidence: 99%
“…Publications from Spain in the last 5 years include reports by Flamarique et al 11,12 on the attitudes of parents and adolescent patients with schizophrenia toward ECT, and a study on the long-term efficacy of ECT in adolescent schizophrenia patients. 13 Examples of publications from France include a comprehensive review on the topic of catatonia with reports of their own samples by Benarous et al, 14 and reports by Consoli et al 8 about ECT in self-harming behavior in adolescents with intellectual disability and patients with schizophrenia. 15 There are also publications from the Netherlands, 16 Belgium, 4 and Germany.…”
mentioning
confidence: 99%